Successful treatment of pulmonary mucormycosis in a child with aplastic anemia - Ye. A. Nikitina; N. N. Klimko; A. S. Kolbin; E. G. Boychenko; I. A. Garbuzova; M. V. Golubeva; T. S. Bogomolova (Онкогематология)
Mucormycosis (zygomycosis) is a frequently fatal fungal infection in immunocompromized patients. We describe a case of a successfull treatment of pulmonary mucormycosis in 11-year-child with a very severe aplastic anemia. The diagnosis of invasive mycosis has been proved according to EORTC 2008 criteria. Computed tomography showed bilobar right-sided pulmonary infiltration. Lichtheimia corymbifera cultured from BAL. The child achieved complete clinical, laboratory and instrumental response on long-term amphotericin B lipid-formulated therapy combined with posaconazole.